Analysis of Financial and Non-Financial Factors on Financial Distress in Brick Industry Energy Sector Companies - Mariani, Desy; Anggraeni, Desy; Said, Said (Ridwan Institute, 2023)
This study aims to predict the incidence of financial distress in a company using financial and non-financial in coal industry energy sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The data used in this study was obtained from financial statements. The sampling technique used was the purposive sampling method and obtained 120 sample data from 24 companies. The analysis technique used in this study is a multiple linear regression analysis by using the Statistical Product and Service Solution (SPSS) version 22 program. The results of this study indicate that leverage has a negative and significant effect on financial distress, operating capacity and operating cash flow has a positive and significant effect on financial distress, while audit committees and institutional ownership have no effect on financial distress.